The importance of healthy eating for the treatment of women of childbearing age with endometriosis: A systematic review (Research, Society and Development, 2024)
Objectives: Objective: The present study carried out a systematic review with the aim of investigating the importance of healthy eating for the treatment of women of childbearing age with endometriosis. Methods: 23 articles were evaluated, being an integrative journal and correlated with articles published in the last 10 years, such as PubMed (National Library of Medicine) and MedLine (Medical Literature Analysis and Retrieval System Online), in the period corresponding to the months of August to November 2023. Results: The results revealed the importance of controlling the diet of women of childbearing age with endometriosis. Choosing a good eating strategy rich in nutrients, antioxidants and carried out exclusively results in a better quality of life. Conclusion: Itis crucial to implement preventive and correct treatment interventions associated with endometriosis. In addition to highlighting the importance of developing a specific and valid nutritional strategy aimed at the health condition of these women.